Isolation, characterisation, anticancer and anti-oxidant activities of 2-methoxy mucic acid from Rhizophora apiculata: an in vitro and in silico studies. Issue 4 (4th March 2023) - Parthiban, A.; Sachithanandam, V.; Lalitha, P.; Muthukumaran, Jayaraman; Misra, Ranjita; Jain, Monika; Sridhar, R.; Mageswaran, T.; Purvaja, Ramachandran; Ramesh, Ramachandran
Abstract: The main objective of the present study is to isolate and characterise the novel bioactive molecule, 2-methoxy mucic acid (4) from Rhizophora apiculate Blume under the Rhizophoraceae family. In this study, the 2-methoxy mucic acid (4) was isolated for the first time from the methanolic extract of the leaves of R. apiculata . Anticancer activity of 2-methoxy mucic acid (4 ) was evaluated against HeLa and MDA-MB-231 cancer cell lines and they displayed promising activity with IC50 values of 22.88283 ± 0.72 µg/ml in HeLa and 2.91925 ± 0.52 µg/ml in the case of MDA-MB-231, respectively. Furthermore, the antioxidant property of 2-methoxy mucic acid (4 ) was found to be (IC50 ) 21.361 ± 0.41 µg/ml. Apart from in vitro studies, we also performed extensive in silico studies (molecular docking and molecular dynamics simulation) on four critical antiapoptotic Bcl-2 family members (Bcl-2, Bcl-w, Bcl-xL and Bcl-B) towards 2-methoxy mucic acid (4) . The results revealed that this molecule showed higher binding affinity towards Bcl-B protein ( ΔG = −5.8 kcal/mol) and the structural stability of this protein was significantly improved upon binding of this molecule. The present study affords vital insights into the importance of 2-methoxy mucic acid (4 ) from R. apiculata . Furthermore, it opens the therapeutic route for the discovery of anticancer drugs. Research Highlights: This is a first report on a bioactive compound identified and characterised; a novel 2-methoxy mucic acid derived from methanolic crude extract from the leaves of R. apiculata from ANI. Estimated binding free energy of 2-methoxy mucic acid is found to be −5.8 kcal/mol to the anti-apoptotic Bcl-B protein. 2-methoxy mucic acid showed both significant anti-cancer and anti-oxidant activity. Communicated by Ramaswamy H. Sarma